Rekindling the flame : principals combating teacher burnout - Brock, Barbara L.; Grady, Marilyn L. (California : Corwin press, Inc., 2004)
This book offers a research-based, practical approach to recognizing, managing, and preventing teacher burnout. It provides a description of the origins and symptoms of burnout and a personality profile of teachers who are most susceptible to burnout. Organizational issues and administrative roles that contribute to burnout are identified, along with suggestions for improvement. There are eight chapters in two parts. Part 1, "The Burnout Syndrome," includes (1) "When the Flame Flickers: Recognizing Burnout," (2) "Flame Extinguishers: Sources of Burnout," and (3) "Smoldering Embers: The Cost of Burnout." Part 2, "Recovery and Prevention," includes (4) "Igniting the Flames: Revitalization Strategies," (5) "Guardian of the Flame: The Principal's Role," (6) "Tending the Flames: Supervision," (7) "Fuel for the Flame: Staff Development as Prevention," and (8) "Stoking the Fire: Improving the Workplace." (Contains 99 references.) (SM).
Includes bibliographical references and index.
Keywords: Teacher -- Job Stress; Burn out (psychology) -- Prevention; Teacher -- principal relationships